Structure of supramolecular astaxanthin aggregates revealed by molecular dynamics and electronic circular dichroism spectroscopy - Zajac, Grzegorz; Machalska, Ewa; Kaczor, Agnieszka; Kessler, Jiří; Bouř, Petr; Baranska, Malgorzata (Physical chemistry chemical physics, 2018)
Biomolecular aggregation is omnipresent in nature and important for metabolic processes or in medical treatment; however, the phenomenon is rather difficult to predict or understand on the basis of computational models. Recently, we found that electronic circular dichroism (ECD) spectroscopy and closely related resonance Raman optical activity (RROA) are extremely sensitive to the aggregation mechanism and structure of the astaxanthin dye. In the present study, molecular dynamics (MD) and quantum chemical (QC) computations (ZIndo/S, TDDFT) are used to link the aggregate structure with ECD spectral shapes. Realistic absorption and ECD intensities were obtained and the simulations reproduced many trends observed experimentally, such as the prevalent sign pattern and dependence of the aggregate structure on the solvent type. The computationally cheaper ZIndo/S method provided results very similar to those obtained by TDDFT. In the future, the accuracy of the combined MD/QC methodology of spectra interpretation should be improved to provide more detailed information on astaxanthin aggregates and similar macromolecular systems.
Keywords: dimerizace; Circular Dichroism; Molecular Structure; Ramanova spektroskopie; simulace molekulární dynamiky; cirkulární dichroismus; Quantum Theory; xanthofyly; Dimerization; Xanthophylls; Molecular Dynamics Simulation; Spectrum Analysis, Raman; kvantová teorie; molekulární struktura